Measuring Antioxidant Activity in Bioorganic Samples by the Differential Oxygen Uptake Apparatus: Recent Advances. (19th March 2017) - Amorati, Riccardo; Baschieri, Andrea; Valgimigli, Luca
Abstract : The measure of O2 consumption during the inhibited autoxidation of an easily oxidizable substrate is one of the most reliable and predictive methods to assess antioxidant activity, especially for structure-activity relationship studies, for food and industrial applications. The differential oxygen uptake apparatus described herein represents a powerful and cost-effective way to obtain antioxidant activity from inhibited autoxidation studies. These experiments provide the rate constant and the stoichiometry of the reaction between antioxidants and peroxyl radicals (R O O ∙ ), which are involved in the propagation of radical damage. We show the operation principles and the utility of this instrumentation in the bioorganic laboratory, with regard to the recent advances in this field, ranging from the study of natural antioxidants in biomimetic system, to the use of substrates generating hydroperoxyl radicals, and to the evaluation of novel nanoantioxidants.